Specificity of in Vivo Confocal Cornea Microscopy in Acanthamoeba Keratitis. Issue 1 (January 2017) - Füst, Ágnes; Tóth, Jeannette; Simon, Gyula; Imre, László; Nagy, Zoltán Z.
Purpose: To report on the presence of 4 different structures visualized by confocal microscopy in patients whose clinical presentation suggested infection by Acanthamoeba . Methods: Data and charts of 28 consecutive patients were analyzed in a retrospective study. Four types of structures were recognized by confocal microscopy performed with HRT II Rostock Cornea Module: trophozoites, double-walled cysts, signet rings, and bright spots. The 28 patients (mean age 30.8 years, range 17-61 years, 10 male, 18 female) were divided into 4 groups according to the diagnosis established later by microscopic examination of smear, culture, response to therapy, and the course of keratitis. The 4 groups were Acanthamoeba keratitis (AK), Acanthamoeba suspect (AK-suspect), bacterial keratitis (BK), and fungal keratitis (FK). Results: The rate of patients in AK, AK-suspect, FK, and BK groups where bright spots were found were 100%, 100%, 40%, and 55%, respectively. The sensitivity of presence of bright spots in the in vivo confocal microscopy in Acanthamoeba keratitis was 100% (95% confidence interval [CI] 73.5% to 100.00%) and specificity was 50% (CI 24.7% to 75.4%). When cases where the only signs of Acanthamoeba were bright spots were excluded, and only those cases were counted where any of cysts, trophozoites, or signet rings were also found, the sensitivity was 67% (95% CI 34. 9% to 90.1%) and the specificity was 94% (95% CI 69.8% to 99.8%). Conclusions: The relatively high rate of bright spots in non- Acanthamoeba keratitis challenges the assumption that bright spots seen by confocal microscopy are a specific indication of Acanthamoeba keratitis.